Exploration of Local Wisdom in Creative Economy Literacy: The Case of Banana Chips Small Business - Iwan Harsono; Muh. Yahya; Andi Naila Quin Azisah Alisyahbana; Rizka Aisyah Nurjannah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2024)
This research aims to explore local wisdom through creative economic literacy in the small banana chip industry in East Luwu Regency. The type of research used is qualitative with the source of informants being 5 people each from small businesses who have different marketing methods in terms of product sales in East Luwu Regency. The data collection technique was carried out in two aspects, namely primary and secondary. The data collected is then processed and analyzed using qualitative descriptive methods, to provide an overview, explanation, understanding and conclusions. The results of the research show that banana chips business actors in East Luwu Regency already understand creative economic literacy with the knowledge they have, they can act or behave in accordance with the knowledge they have gained from the learning process and from training. They run their business with the knowledge they get from the process of selecting raw materials to how they market their products. Potentially, the creative economy industry can be used as an alternative to restore the economic conditions of society which are starting to decline.